An Adaptive Control Technique for Motion Synchronization by On-line Estimation of a Recursive Least Square Method - Lee, Sang-Deok; Jung, Seul (International journal of control, automation, and systems, 2018)
This article presents an adaptive technique to tune controller gains for the motion synchronization of two gimbal systems by using a recursive least square method in the real-time fashion. In the master-slave configuration, the slave gimbal system follows the master’s motion while the master tracks the reference. In order for the slave gimbal system to synchronize with the motion of the master gimbal system, the dynamic difference between two systems is compensated by the controller gains. The controller gains of the slave are adaptively adjusted by the recursive least square method to cope with the deviation. The performances of three control schemes such as an independent PD control, a dependent torque control, and an RLS torque control scheme are evaluated by the experimental studies for the low cost gimbal systems. Experimental studies confirm that the RLS-based adaptive scheme actually outperforms by adjusting controller gains for the motion synchronization of the master and slave configuration.